Australian Water Dragons - Mitchell, Lisa (Brisbane, Queensland : Lisa Mitchell, 2019)
Australian Water Dragons are wonderful native animals found exclusively in Eastern Australia. These beautiful lizards have unique qualities and characteristics. Readers will love learning about these 'dinosaur-like' reptiles, which come from an ancient line of lizards. Interesting facts include: identifying features, communication, sloughing of scaly skin, parietal eye, regenerative bifurcation supplemented with a labelled CT Scan (skinks tail), territory, combat, brumation, reproduction, life cycle, further reading links, QR Codes and much more! Within these pages are 37 vivid, colourful photographs to enjoy!
Keywords: Lizards -- Australia; Reptiles -- Australia; Water dragons (Reptiles); Lizards; Reptiles; Water dragons (Reptiles); Australia